Literasi Digital Masyarakat dalam Pemanfaatan Pelayanan Publik Berbasis Digital di Badan Pusat Statistik Kota Tomohon - Yosirdam Idaman; Devie S. R. Siwij; Brain Fransisco Supit (Tumoutou Social Science Journal, 2026)
The transformation of public services toward digital-based systems will not yield optimal benefits unless accompanied by community readiness to operate and meaningfully use such services. This study aims to describe community digital literacy in utilizing digital-based public services at the Central Bureau of Statistics (BPS) of Tomohon City and to identify the factors that hinder its implementation. This research employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving the Head of BPS Tomohon City, integrated statistical service officers, and service users, then analyzed through data reduction, data display, and conclusion drawing, with validity examined through source and method triangulation. The findings reveal that community digital literacy in utilizing digital-based public services at BPS Tomohon City remains suboptimal. Although the community is able to access digital services and obtain information online, difficulties remain in understanding service procedures, evaluating digital information, and independently utilizing available service features. The main inhibiting factors include limited technological skills, inadequate understanding of digital services, insufficient socialization, and differences in educational background and technological experience among service users. The study concludes that improving community digital literacy through continuous education, training, and socialization is an essential precondition for more effective, inclusive, and accessible digital-based public services